Architecture: a new human and technical relationship in the face of climate change. - Forero, Boris (Artes: Architecture, Technology and Sustainability, 2022)
Having become an eminently urban species brings with it the already known impacts that feed the main greenhouse effect that causes the phenomenon of climate change. By 2020, activities linked to the construction industry, as well as architectural design, contribute about 38% of Greenhouse Gas – GHG emissions worldwide. The operation of buildings on a global scale, consume 35% of the energy produced worldwide, thus highlighting the responsibility that the architectural design activity has in this scenario. The discussion and reflections of the relationship of the human being and nature, understood as new ways of approaching through political ecology. Nature is now a creditor of rights, which traces a path of constant interaction between the parties involved as technological advances and the discipline of architecture.